The Effect of Tax Avoidance on Cost Of Debt with Institutional Ownership as Moderating Variable - Dhear Sari Artana, Putu; Supadmi, Ni Luh (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2025)
This study aims to examine the effect of tax avoidance on the cost of debt and also examine the effect of institutional ownership in moderating the relationship between tax avoidance on the cost of debt in mining companies listed on the Indonesia Stock Exchange. The research design is structured as quantitive research. The number of observations was 30 companies using purposive sampling method. The researcher’s analysis technique is multiple linear regression. The result of the study show that the tax avoidance variable has no effect on the cost of debt. Meanwhile, institutional ownership cannot moderate either strengthen or weaken the effect of tax avoidance on the cost of debt. The implications of this study is to assist the Director General of Taxes in identifying tax avoidance practices, provide more in-depth information about tax avoidance for taxpayers, and to offer insights related to tax avoidance on the cost of debt.